Impact of Covid-19 Pandemic on the Effectiveness of Outpatient Counseling in Childhood Obesity Management - Corica, Domenico; Li Pomi, Alessandra; Curatola, Selenia; Pepe, Giorgia; Giandalia, Annalisa; Tropeano, Angelo; Alibrandi, Angela; Aversa, Tommaso; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2022)
The Covid-19 pandemic drastically modified social life and lifestyle, in particular, among children and adolescents, promoting sedentary behaviors and unhealthy eating habits. The aims of this study were to assess the rate and the factors associated with outpatient drop-out in childhood obesity management, and to evaluate how the Covid-19 pandemic influenced weight status and lifestyle of children and adolescents with obesity. One hundred and forty-five children and adolescents with obesity were identified, including 80 subjects evaluated before the Covid-19 pandemic (group A) and 65 subjects in the period straddling the Covid-19 pandemic (group B). Anamnestic (family history of obesity, dietary habits, physical activity, screen time), socio-cultural (economic status, employment and schooling of parents, household composition, place of living) and clinical (weight, height, BMI, waist circumference) data were retrospectively analyzed for each subject in both groups at baseline (V0) and 12-months (V1) at in-person assessment. Glycemic and lipid profiles were assessed at V0. Drop-out rate did not differ significantly between the two groups. BMI SDS at V0 (OR=2.52; p=0.004), female sex (OR=0.41; p=0.035), and the presence of a single parent in the household (OR=5.74; p=0.033) significantly influenced drop-out in both groups. Weight loss between V0 and V1 was significantly greater among group A patients compared to group B (p=0.031). In group B, hours spent in physical activity significantly decreased from V0 to V1, being significantly lower than group A at V1; on the contrary, screen time significantly increased in the same period. The consumption of sugary drinks and snacks was significantly greater in group B than group A at V1. Our study documented that the Covid-19 pandemic, although not affecting the drop-out rate of obese children in a follow-up program, negatively influenced lifestyle and reduced the effectiveness of outpatient counseling in childhood obesity treatment.